PENGGUNAAN INTERNET DAN PENGEMBANGAN DIRI SISWA MAN 1 PEKANBARU - Rani, Saida; Umari, Tri; Rosmawati, Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Internet represent a computer network and connective world between consumer one and other consumer without dissociated distance. All its consumer can access various need of education, information, communications and various other area. Positive impact in usage of internet that is watering down in communicating between its consumer, watering down in changing over data between consumer of internet, watering down in transacting, watering down its consumer in obtaining information. Internet also give negative impact to its consumer that is by watering down obtain; get various information, also easy for its consumer for the mengakkses of pornography able to immorality, the happening of deception through internet and gambling of online. But internet represent free media of value, on the other side can be positive useful and on the other side can affect the mentioned negativity depended from its consumer. The use of internet give various benefit and amenity to its consumer and development of self to fulfill requirement of self actualization. The purpose of this study are: 1. To find out description of the internet use in MAN 1 Pekanbaru 2. To find out description development of student self of MAN 1 Pekanbaru. This Research use quantitative method with descriptive approach and technique of simple sampling random. Result of this research indicate that usage of internet reside in high category 94 people or 54%. equal to development of self reside in high category 63%. This matter indicate that development of student x'self in MAN 1 Pekanbaru very good. Knowable that student can develop x'self by exploiting internet wisely.Key Words : Self Development, The use of internet